Utilization of Family Planning Services in Karnali Academy of Health Science, Jumla - Dr. Sharmila Shrestha (Journal of Karnali Academy of Health Sciences, 2019)
Introduction: Family planning is an integral part of maternal health as its uptake is a significant factor in the reduction of maternal mortality and in ensuring positive child health outcomes specially in developing countries, however, its usage remains low.